Deep Neural Networks with Application to Transformer Failure Diagnosis - Moraes, Hugo Riviere S.; Castro, Adriana Rosa Garcez (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e Computacional, 2018)
This paper presents the outcomes of an application research of deep neural networks to diagnosis incipient faults in power transformer through dissolved gas-in-oil analysis (DGA). Two models was proposed, first, using a Stacked Autoencoder Network and later a Convolucional Neural Network. To the development of the system was used the database TC10 which contains data of faults usually found in electrical equipment in service. This database are described in norm IEC 60599. The outcomes achieved, considering the testing data was 100% and 96,5% of accuracy, showed that this models containing a wide applicability to the problem.